PERLINDUNGAN HUKUM TERHADAP DATA PRIBADI PENUMPANG PESAWAT UDARA (Studi Kasus Terungkapnya Data Penumpang Malindo Air) - Elsa Halida Saputri (Fakultas Hukum Universitas Sebelas Maret, 2023)
This article aims to assess the protection carried out by airlines for airplane passengers if they failed to protect their personal data. Methode used in this article is a sociological or empirical legal research method named descriptive, and the approach research used a qualitative approach that produces descriptive data. In this case of laws used source of invitation primary legal materials and secondary legal materials by means of literature studies and interviews. Data analysis technique used is qualitative analysis with qualitative methods. This law written to shows that apart from the existence of legal responsibility as well as ethical responsibility which aims to retain consumers, by revising the contents of the work agreement between Malindo Air and GoQuo. Malindo Air itself manages all consumer passwords automatically and urges consumers to change the password used for Malindo Miles. Malindo Air and GoQuo also reported 2 (two) former GoQuo employees who have distributed Malindo Air passanger personal data.Key words: personal data; flight protection measures; Malindo Air